MiR181c promotes apoptosis and suppresses proliferation of metanephric mesenchyme cells by targeting Six2 in vitro. (3rd September 2014) - Lv, Xiaoyan; Mao, Zhaomin; Lyu, Zhongshi; Zhang, Pengzong; Zhan, Alan; Wang, Jian; Yang, Hui; Li, Mi; Wang, Honglian; Wan, QianYa; Wei, Hongyuan; Wang, Ming; et al.
<x xml:space="preserve">Abstract</x> Increasingly recognized importance has been assumed for microRNA (miRNA) in the regulation of the delicate balance of gene expression. In our study, we aimed to explore the regulation role of miR181c towards Six2 in metanephric mesenchyme (MM) cells. Bioinformatics analysis, luciferase assay and semi‐quantitative real‐time (RT) PCR, subsequently RT PCR, Western blotting, 5‐ethynyl‐2′‐deoxyuridine cell proliferation assay, Cell Counting Kit‐8 assay, immunofluorescence and flow cytometry, were employed to verify the modulation function of miR181c on Six2 in the mK3 MM cell line that is one kind of MM cells. miR181c was predicted to bind the 3′ untranslated region of Six2 by bioinformatics analysis, which was subsequently validated by the in vitro luciferase reporter assay. Moreover, transfection of miR181c mimic can decrease the expression of Six2 both in mRNA and protein levels in mK3 cells. Still, ectopic expression of miR181c inhibits the proliferation, promotes the apoptosis and even makes the nephron progenitor phenotype lose mK3 cells. These results revealed the ability of a single miRNA–miR181c to downregulate the expression of Six2, restrain the proliferation and promote the apoptosis that even makes the nephron progenitor phenotype lose MM cells, suggesting a potential role of miR181c during the kidney development. Copyright © 2014 John Wiley & Sons, Ltd.